An empirical investigation of calls of non-convertible bonds - Vu, Joseph D. (Journal of Financial Economics, 1986)
This paper examines call behavior of corporate issuers of non-convertible bonds. Evidence from a sample of 102 calls indicates that the market value of the called bonds is usually below the call price at the time of the announcement. The stock price reactions to call announcements are positively related to the direction of the change in leverage. When the call relaxes restrictive covenants, the firm on average pays a larger premium to call debt. The premium is a minimum estimate of the potential opportunity costs of restrictive covenants.